Development of SnO2@rGO Hybrid Nanocomposites through Complexometric Approach for Multi-Dimensional Electrochemical Application. Issue 16 (11th December 2020) - Raj, Benjamin; Oraon, Ramesh; Mohapatra, Mamata; Basu, Suddhasatwa; Padhy, Arun K
Abstract : Herein, we report a time-efficient one pot preparation of SnO2 and its composite with reduced graphene oxide (rGO) using Imidazole based organic precursor followed by calcination. Various physicochemical analyses (viz. FT-IR, XRD, XPS etc.) confirmed the successful formation of SnO2 immobilized @rGO nanocomposite. Improved surface microstructural evolution with a uniform decoration of SnO2 over rGO (in composite) was observed via SEM, EDAX analysis. The enhanced surface area of SnO2 @rGO nanocomposite material from 120 m 2 g −1 of pure SnO2 to 145 m 2 g −1 after incorporation with rGO provides a shorter diffusion path for electrolyte and better charge transfer property. Electrochemical measurements via cyclic voltammetry (CV) revealed tremendous increase (∼344%) in specific capacitance of SnO2 from 32.80 F g −1 to 112.87 F g −1 in composite with rGO. These observations were well complemented by EIS analysis with improved charge transfer property of SnO2 @rGO nanocomposite. Furthermore, amperometric curve ( i-t ) showed that SnO2 @rGO nanocomposite material exhibited an excellent electrocatalytic activity towards non-enzymatic glucose sensor with a low detection limit of 6.4 nM, a wide linear range of 20 μ M–380 μ M (R 2 = 0.908) and high sensitivity (0.2127 μ A mM −1 cm −2 ), respectively.